Pengembangan Media Pembelajaran Interaktif Pemrograman Dasar Kelas X Sekolah Menengah Kejuruan di SMK PGRI 3 Malang dengan Mengadaptasi Model APPED - Agung Witanto; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malang City has Vocational High Schools that have the most complete ICT A accreditation for RPL majors, one of which is Vocational High Schools PGRI 3 MALANG. This school uses ICT that interact with each other, and innovate to produce students majoring in Software Engineering with work-ready knowledge in the industrial world. However, this is inversely proportional to the lack of use of learning media in the basic programming material of the flowchart chapter for students to learn, so a prototype of interactive learning media was made by adapting the APPED model. This model has stages in the form of analysis & preliminary research, design, production, evaluation, & dissemination. The dissemination stage was not carried out because the learning media made were prototypes. In media development, Adobe Animated software is needed as a means of prototyping learning media in flash form. The results of the alpha test from the experts' test stated that the material in this media was very good with a percentage of 95.5%, for media it was considered very good with a percentage of 88.8% and for instructional in the media it was assessed as 92.5%. With these results it is stated that this media can be used properly.